Comparison of pulmonary inflammatory responses following intratracheal instillation and inhalation of nanoparticles. Issue 5 (27th May 2016) - Morimoto, Yasuo; Izumi, Hiroto; Yoshiura, Yukiko; Tomonaga, Taisuke; Lee, Byeong-Woo; Okada, Takami; Oyabu, Takako; Myojo, Toshihiko; Kawai, Kazuaki; Yatera, Kazuhiro; Shimada, Manabu; Kubo, Masaru; et al.
Abstract: In order to examine whether intratracheal instillation studies can be useful for determining the harmful effect of nanoparticles, we performed inhalation and intratracheal instillation studies using samples of the same nanoparticles. Nickel oxide nanoparticles (NiO) and titanium dioxide nanoparticles (TiO2 ) were used as chemicals with high and low toxicities, respectively. In the intratracheal instillation study, rats were exposed to 0.2 or 1 mg of NiO or TiO2 . Cell analysis and chemokines in bronchoalveolar lavage fluid (BALF) were analyzed from 3 days to 6 months following the single intratracheal instillation. In the inhalation study, rats were exposed to inhaled NiO or TiO2 (1.65, 1.84 mg/m 3, respectively) for 4 weeks. The same endpoints were examined from 3 days to 3 months after the end of exposure. Inhalation of NiO induced an increase in the number of neutrophils in BALF and concentrations of cytokine-induced neutrophil chemoattractant (CINC)-1, CINC-2 and heme oxygenase (HO)-1. Intratracheal instillation of NiO induced persistent inflammation and upregulation of these cytokines was observed in the rats. However, inhalation of TiO2 did not induce pulmonary inflammation, and intratracheal instillation of TiO2 transiently induced an increase in the number of neutrophils in BALF and the concentrations of CINC-1, CINC-2 and HO-1. Taken together, a difference in pulmonary inflammation was observed between the high and low toxicity nanomaterials in the intratracheal instillation studies, as in the inhalation studies, suggesting that intratracheal instillation studies may be useful for ranking the harmful effects of nanoparticles.